2012
DOI: 10.12697/akut.2011.17.15
|View full text |Cite
|
Sign up to set email alerts
|

Knee pain and postural stability in women with gonarthrosis before and six months after unilateral total knee replacement

Abstract: The aim of this study was to investigate knee pain and postural stability in women with knee osteoarthritis (OA), who used postoperative home exercise program (HEP) with balance exercises. 14 women with knee OA in stage III-IV (aged 48-70 years) participated in this study before and 6 months after unilateral total knee arthroplasty (TKA). All patients performed HEP during 6 months after unilateral TKA. Data of patients was compared with healthy age-matched women (controls, n=10). Postural stability characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Full recovery of muscle strength and physical function to a normal level is rare (10,12) and impairments may persist several years after surgery (17)(18)(19)(20). In addition, these impairments can lead to reduced balance and movement control (21,22) and a greater risk of falling (22,23). Neuromuscular performance capabilities are altered significantly in people with arthritis, and impairments are evident pre-operatively (24).…”
mentioning
confidence: 99%
“…Full recovery of muscle strength and physical function to a normal level is rare (10,12) and impairments may persist several years after surgery (17)(18)(19)(20). In addition, these impairments can lead to reduced balance and movement control (21,22) and a greater risk of falling (22,23). Neuromuscular performance capabilities are altered significantly in people with arthritis, and impairments are evident pre-operatively (24).…”
mentioning
confidence: 99%
“…These findings are in agreement with previous research. A study by Rätsepsoo et al [56] found a significant association between quadriceps strength and postural stability in individuals with knee OA. Similarly, a study by Hinman et al [57] reported a relationship between muscle strength and functional performance in individuals with knee OA.…”
Section: Discussionmentioning
confidence: 98%
“…Снижение силы четырехглавой мышцы бедра оказывает существенное влияние на изменение статического и динамического постурального баланса [17,45] и повышает риск падения пациентов [45]. Это, в свою очередь, потенцирует увеличение частоты неблагоприятных результатов эндопротезирования коленного сустава.…”
Section: результаты и их обсуждениеunclassified